PENGARUH KOMPETENSI AUDITOR TERHADAP KINERJA AUDITOR (Studi Pada Inspektorat Provinsi Sulawesi Tenggara) - Nurnaluri, Sitti; Cahyaniza, Cahyaniza (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
ABSTRACTÂ The aims of the study was to examine the effect of competence of auditor to auditorâs performance at Inspectorate of South East Sulawesi Province. The primary data in this study was abtained from the all auditorâs perception at the Inspectorate of South East Sulawesi Province. Respondents perceptions measured by the answer of questionnaires used ordinal measurement with 5 Likert scale. The statistical methods used to test each hypothesis was simple linear regression analysis.The results of the study showed that competence of auditor gave positive and significant effect toward auditorâs performance. The total coefficient of determination showed that the contribution competence of auditor on the auditorâs performance was 78,1%, while the rest 21,9% obtained from the contribution of other factors.Â Keywords : Competence of Auditor and Auditorâs Performance.